Comparison of Shear Bond Strength of Three Types of Glass Ionomer Cements Containing Hydroxyapatite Nanoparticles to Deep and Superficial Dentin - Farahnaz Sharafeddin; Ali Asghar Alavi; Saba Siabani; Mina Safari (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: The clinical success of glass ionomer cement (GIC) restorations depends on the strength of its bonding to dentin, yet the bond strength of nanohydroxyapatite (nHAp) added GIC to dentin needs to be investigated. Purpose: This study aimed to assess if the type of GIC containing nHAp and dentin depth could affect the shear bond strength (SBS). Materials and Method: In this experimental study, 60 freshly extracted intact third molars were randomly divided into two main groups of flat occlusal dentin with different cuts as superficial (S); just below the dentinoenamel junction (DEJ) and deep (D); 2mm below DEJ. After conditioning with 20% polyacrylic acid, each group were randomly assigned to the tested GIC (n=10) subgroups as (1) Fuji IX Extra+nHAp, (2) Fuji II LC+nHAp and (3) Zirconomer+nHAp. Plastic tubes were placed on the pre-treated surfaces and filled with one of the GIC, then stored in an incubator at 37 oC and 100% humidity for 24hr. The specimens were thermocycled at5/55 oC for 500 cycles and subjected to SBS test using a universal testing machine (1 mm/min). The data analyzed by Mann-Whitney and Kruskal-Wallis test (p< 0.05). Results: The means of SBS of Fuji II LC+nHAp was significantly higher than Fuji IX+nHAp and Zirconomer+nHAp both in superficial and deep dentin (p< 0.05). The means of SBS of Fuji IX Extra+nHAp and Zirconomer+nHAp subgroups in superficial dentin were higher than deep dentin, this differences was statistically significant (p= 0.0001 and p= 0.009, respectively). Conclusion: It can conclude that SBS was influenced by type of GIC and depth of dentin.